Tourism Resilience and Sustainable Development: Evidence from Bali, Indonesia - Ida Bagus Putra Setiawan (Bali Tourism Journal, 2025)
Tourism is a highly dynamic yet vulnerable sector, particularly in destinations with strong dependence on international travel. The COVID-19 pandemic exposed structural weaknesses in mass tourism systems and highlighted the urgent need for resilience-oriented development pathways. This study examines the relationship between tourism resilience and sustainable development in Bali, Indonesia, a destination significantly affected by global tourism disruptions. Adopting a qualitative descriptive research design, the study synthesizes peer-reviewed literature addressing tourism resilience across multiple analytical levels, including governance, community-based systems, and micro, small, and medium-sized enterprises (MSMEs). A thematic synthesis approach is employed to identify patterns of recovery, adaptation, and transformation within Bali’s tourism system. The findings demonstrate that tourism resilience in Bali emerges from interconnected, multi-level processes rather than isolated interventions. Adaptive governance mechanisms enable flexible crisis management and policy learning, while community-based and culturally embedded institutions, such as the Subak system and tourism villages, strengthen social cohesion and environmental stewardship. At the economic level, the psychological and entrepreneurial resilience of MSMEs plays a crucial role in sustaining livelihoods and fostering innovation during prolonged crises. These dimensions collectively reinforce the social, environmental, and economic pillars of sustainable tourism development. Resilience should be understood not merely as a short-term recovery response but as a core principle of sustainable tourism development. Integrating adaptive governance, community empowerment, and business capacity-building is essential to reducing vulnerability and supporting long-term sustainability in highly tourism-dependent destinations such as Bali.